Bank of America : consumers fight back - Walker, Russell, 1972- (SAGE Knowledge. Cases., 2017)
On October 6, 2011, President Barack Obama publicly scolded Bank of America for developing a new revenue stream: a $5 monthly fee for all Bank of America debit card holders, which the bank had announced a month earlier. It was a strategy for replacing lost swipe fee revenue following the passage of the Dodd-Frank Act and accompanying Durbin Amendment, which capped swipe fees at 21 cents per transaction. This was the culmination of three tumultuous years for the world's largest financial services firm, but would not be the end of its public affairs challenges.The president's public critique of Bank of America came in response to and helped exacerbate consumer anger about the banks monthly fee, changes across the banking sector, and general discontent with Wall Street. Bank of America's situation was complicated further by ongoing legal action following acquisitions of Merrill Lynch and Countrywide, which hurt the firms shareholders and led to large-scale employee layoffs. In this case study, students will be challenged to analyze how Bank of America could have better managed the competing interests of different stakeholders, including shareholders, employees, regulators, customers, and the public.